Teaching composing - Coles, William E. (Rochelle Park, N.J.: Hayden Book Co., 1974)
A teacher's ed. for the author's textbook: Composing: writing as a self-creating process.
Keywords: English language -- Rhetoric -- Study and teaching; Creative writing (Higher education)